Sodium carbonate and sodium silicate promote the Ca-montmorillonite: the nucleation, stabilization and hydrophilicity mechanisms - Yin, Chenglong; Huang, Jin; Deng, Shao-yu; Ma, Chong; Peng, Yong (Frontiers in Chemistry, 2025)
Montmorillonite is widely utilized in catalysis, environmental science, and civil engineering. Previous studies have demonstrated that Na2CO3 and Na2SiO3 enhance the stability of Ca-montmorillonite-rich clayey soils in chemical soil stabilization. However, the microscopic mechanisms underlying their effects on nucleation, stabilization, and hydrophilicity remain unclear. This study investigates these mechanisms using Scanning Electron Microscopy (SEM) and Density Functional Theory (DFT) calculations. SEM results show that Na2CO3 and Na2SiO3 enhance the strength of the stabilized soils by promoting the formation of cementitious and crystalline substances. DFT calculations reveal that SiO32- and CO32- exhibit the most negative adsorption energies of −6.2 eV and −5.1 eV, respectively, in the exchangeable layers of montmorillonite, significantly higher than those of Na+ and Ca2+. On the montmorillonite surface, SiO32- and CO32- display even lower adsorption energies of −8.7 eV and −6.8 eV, respectively. Water molecules preferentially adsorb dissociatively on the montmorillonite surface with an energy of −3.1 eV; however, their adsorption is suppressed following the adsorption of Ca2+, Na+, CO32-, and SiO32-, with energies decreasing to between −1.1 eV and −2.5 eV. Differential charge density plots indicate that ion adsorption leads to charge redistribution and the formation of chemical bonds. Specifically, Ca2+ and Na+ donate cationic charge, while CO32- and SiO32- accept electrons. The study further explains why Na2CO3 and Na2SiO3, in combination with lime, are more effective than lime alone in soil stabilization. A mechanism model for nucleation, stabilization, and hydrophilicity is proposed to explain the role of Na2CO3 and Na2SiO3 in promoting Ca-montmorillonite stabilization. This work provides valuable insights into the chemical properties of montmorillonite and the synergistic effects of calcium-based stabilizers combined with Na2CO3 and Na2SiO3 for soil stabilization.